Gaucher disease type 2 (case report) - D. R. Shagieva; R. V. Magzhanov; A. R. Rakhmatullin; E. V. Sayfullina; R. G. Musin (Русский журнал детской неврологии, 2020)
The article describes a rare clinical case of Gaucher disease in a 5 month old girl, confirmed by molecular genetic analysis. In the presented clinical case, there is a onset of lysosomal accumulation disease, which is accompanied by changes in the clinical analysis of blood (anemia, thrombocytopenia), hepatosplenomegaly, congenital malformations (open arterial duct, open oval window) and severe neurologic deficit.